2011
DOI: 10.1002/acr.20427
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of design and effects of splints and exercise programs in hand osteoarthritis

Abstract: Objective. To describe and evaluate the design and effects of splints and exercise programs in hand osteoarthritis. Methods. Controlled trials identified through systematic literature reviews were included. Design of splints and exercise programs were evaluated according to existing recommendations and classification systems. The risk of bias was assessed by 2 independent reviewers and effects were summarized descriptively or by meta-analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 52 publications
4
82
0
9
Order By: Relevance
“…Conservative intervention is indicated as a first approach for OA of the CMCJ and comprises a range of assessment and intervention options which are fully outlined in the occupational therapy literature and usually comprises splinting, the application of joint protection principles and strengthening of the thenar eminence as well as the hand and wrist musculature [9][10][11][12] . The literature indicates however that the Eaton and Glickel's classification of OA of the CMCJ, is still used in practice today despite a lack of inter -and intra-observer reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative intervention is indicated as a first approach for OA of the CMCJ and comprises a range of assessment and intervention options which are fully outlined in the occupational therapy literature and usually comprises splinting, the application of joint protection principles and strengthening of the thenar eminence as well as the hand and wrist musculature [9][10][11][12] . The literature indicates however that the Eaton and Glickel's classification of OA of the CMCJ, is still used in practice today despite a lack of inter -and intra-observer reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on these studies Valdes and Marik concluded that joint protection principles, assistive devices and the application of heat is supported in the literature as valuable in the conservative intervention of OA of the CMCJ 9 . Further evidence for the use of a conservative approach was provided by Kjeken, Smedslund and Rikke in their systematic review in 2011 10 . They determined the effectiveness of splinting and an exercise regimen in the reduction of symptoms of OA of the CMCJ of the thumb.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Valdes and Marik [23] examined 21 studies on conservative treatments and found evidence to support the use of orthotics, hand exercises, application of heat, or joint protection education combined with adaptive equipment to improve grip strength and function. Kjeken et al [11] reviewed 12 studies and found consistent evidence that splints reduce hand pain. In contrast to the literature on preoperative hand therapy for hand arthritis, to our knowledge, there has been no systematic review on postoperative hand therapy interventions for basal joint arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Hand is the important part of body to perform the complex daily living, although it is small of many parts of body [6]. Most of daily activity depends on the proper function and it can be easily injured because of its characteristics such as complexity of structure and exposed part.…”
Section: Introductionmentioning
confidence: 99%